Frequency Analysis of Runoff Volume from small Shivalik Watersheds - Agnihotri, Y.; Bagai, O.P.; Dhruvanarayana, V.V. (Journal of Soil and Water Conservation, 2022)
Estimation of monthly and seasonal runoff from small watersheds, which is often required for planning of water harvesting tanks and ponds, has been attempted with the help of normal, lognormal, modified lognormal, log Pearson type III and extreme value distributions in five small Shivalik watersheds. The results showed that normal, lognormal and extreme value distributions gave the best fit to runoff volume data during July, August and September, respectively. The seasonal runoff was, however, best estimated with the help of extreme value distribution.